Simbolis Bentuk Dan Seni Hias Pada Istana-Istana Raja Bugis Sulawesi Selatan - Yunus, Pangeran Paita; Soedarsono, R.M.; -, Sp. Gustami (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2011)
The cosmologic view of the Buginese tribe assumes that this macrocosmos (the universe) is arranged into three levels: Boting langi (the upper world), Ale kawa (the middle world), Uri’ Li’yu’ (the Under world). As the centre from the three parts of this universe is Boting Langi (the highes sjy), the place of Dewata SeumaE (God) to lie down. This view is represented in the traditional house building seen as the microcosmos. So, the traditional house of the Buginese is devided also into three levels (stacks), those are: Rekkeang (top floor) viewed as the head of the human being, Alle bola (the body of the house) viewed as the body, and Awabola (space underneath of the house) viewed as the leg of the human being. The three parts are centered at Posi bola or the house navel. The result of this research is hoped to enrich the knowledge treasury in the art sector, mainly the plastic arts related to the decorated arts obtained in the Buginese kings’ palace. Keyword: decorated art, Buginese tribe.